PENENTUAN CRITICAL CONTROL POINT (CCP) PADA PROSES PRODUKSI ROTI KEJU PT. AEROFOOD ACS YOGYAKARTA - , ANGGIT PRASTIWI ABINENO; , Arita Dewi Nugrahini, STP., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Food safety is an important issue in the food industry because consumers need assurance if they want to consuming some food. Aerofood ACS Yogyakarta is a food processing company engaged in the sector of catering also holds the responsibility as a result of the risk of food insecurity on Roti Keju and their other food products. One of the food quality assurance system to ensure food safety ranging from raw materials to final product that ready to be served is the Hazard Analysis Critical Control Point (HACCP). This final paper arranged in order to define the hazardous possibilities that may found in the main composition, addition, and other supporting composition which used on the process of Roti Keju production, define Critical Control Point (CCP) on each process of Roti Keju production. The results of this final paper is in the process of making Roti Keju, the conclusion that can be taken is: the hazardous possibilities that may be found like